Drought Induced Signaling in Rice: Delineating Canonical and Non-canonical Pathways - Dash, Prasanta K.; Rai, Rhitu; Rai, Vandna; Pasupalak, Surendranath (Frontiers in Chemistry, 2018)
Drought induced stress is often a bottleneck of agricultural crop production. Invariably, all field crops across all agro-ecological regions succumb to it with an yield penalty. Drought massively affects the growth and harvestable yield in crops and has become an imminent problem necessitating breeding of tolerant crops. It induces myriad changes of biochemical, molecular, and physiological nature that manifest into aberrant plant morphology. The response to drought in plants incites a signaling cascade that involves perception and translation of drought signal leading to concomitant modulation of gene expression and de novo osmolyte synthesis. The intricate patterns of expression of these genes vary from early induction to late responsive genes. While one class of genes codes for products imparting osmotolerance and protection to plants, the second class predominantly modulates target gene expression by an intricate signal transduction mechanism. This review summarises both canonical and non-canonical cascades of drought stress response in plants, delineating the mechanism in rice (Oryza sativa) and emphasizes hydropenia induced lipid signaling.